Cerebral Hemangioblastoma Without Von Hippel-Lindau Syndrome: A Report of 6 Cases. (April 2021) - Qu, Limei; Lv, Chuanqi; Ji, Tiefeng; Wang, Yinping; Yu, Jinlu
Background . Hemangioblastoma occurs mainly in the cerebellum and rarely in the cerebrum. Objective . The present study aimed to analyze the clinical manifestations and radiological and pathological features of cerebral hemangioblastoma, and to improve the recognition of this tumor and avoid misdiagnosis. Methods . The characteristics of 6 patients with cerebral hemangioblastoma were analyzed, and a retrospective review of cerebral hemangioblastoma reported in the literature was performed. Results . All 6 patients were female, aged from 22 to 70 years (55 years on average), and all cases were wild-type sporadic, in which 4 cases occurred in the frontal lobe and 2 cases occurred in the parietal lobe. Imaging revealed a solid tumor in 4 cases, a cystic tumor in 1 case, and a mixed tumor in 1 case. Microscopically, the morphology and immunophenotype of tumor cells were not different from those of classical hemangioblastoma. All 6 patients survived tumor free during the follow-up period. Conclusions . Cerebral hemangioblastoma often simulates the imaging characteristics of meningioma or glioma. Enough attention should be paid to differential diagnosis before the operation, and exact diagnosis relies on the pathological examination.